Math, asked by richitavermadpsv, 3 months ago

((√7+√2)(2√2)-3√7) simplify​

Answers

Answered by IlMYSTERIOUSIl
27

simplify :-

{\sf{:\implies( ( \sqrt{7}  +  \sqrt{2} )  (2 \sqrt{2} ) - 3 \sqrt{7}  )}}

{\sf{:\implies( 2 \sqrt{7}  + 2 \sqrt{2} )  ( \sqrt{2} ) - 3 \sqrt{7}  )}}

{\sf{:\implies 2 \sqrt{7}  \sqrt{2}  + 2( \sqrt{2} )^{2}  - 3 \sqrt{7}  }}

{\sf{:\implies 2 \sqrt{14}  + 2( \sqrt{2} )^{2}  - 3 \sqrt{7}  }}

{\sf{:\implies 2 \sqrt{14}  + 2 \times {2}  - 3 \sqrt{7}  }}

{\sf{:\implies 2 \sqrt{14}  + 4  - 3 \sqrt{7}  }}

{\sf{:\implies 2 \sqrt{14}  + 4  - 3 \sqrt{7} ≈  \green{ 3.5460684 } }}

:)

Attachments:
Similar questions